ANALISIS FAKTOR INTERNAL YANG MEMPENGARUHI PROFITABILITAS BANK KONVENSIONAL - Matondang, Khairani Alawiyah; Wijaya, Meisha Fatma; Handayani, Siti Alifah; Simanjuntak, Tessalonika Federova Br (Jurnal Review Pendidikan dan Pengajaran, 2024)
The purpose of this study is to determine the effect of Loan Deposit Ratio (LDR), Net Interest Margin (NIM), and Operational Income Operating Costs (BOPO) on Return on Assets (ROA) in conventional banking sector companies in Indonesia, using 5 banks with financial reports from 2018 to 2022 and complete data on the variables studied. E-Viws 12 technical analysis entails picking a panel data model (common effect, fixed effect, and random effect) and then running a panel data test. According to the findings of the analysis, the net interest margin (NIM) and Operational Income Operating Costs (BOPO) have a partial effect on ROA, however the loan deposit ratio (LDR) has no partial effect on ROA. The elements Loan Deposit Percentage.